The physicochemical characterization of fluoropolymer-modified polysiloxane coatings - Dobkowski, Z.; Zielecka, M. (Polimery, 2022)
A polymer hybrid system, containing a crosslinked polysiloxane (SIL) and fluoropolymer (PTFE), was developed and it has been applied as the antigraffiti coatings. Surface physicochemical properties of the system were investigated, using the tensiometry to determine surface wetting properties, such as the dynamic contact angle (DCA), the X-ray photo-electron spectroscopy for the surface chemical analysis (ESCA/XPS), and the atomic force microscopy (AFM) to observe the surface morphology and roughness. Then, the surface free energy (SFE) and its polar and dispersive parts were calculated from DCA data, as well as the surface elemental composition: F, C, Si, O, in particular the Si and F atoms distributions in the surface layers (XPS), and the roughness parameters of the surface (AFM). It has been found that the following factors are crucial for applications of the SIL/PTFE system as coatings for permanent protection of building materials against graffiti paintings: (a) the wettability, it should be low, (b) the chemical composition, an excess of F atoms at the surface is required, (c) the morphology of surface layers, i.e., tightly packed small domains and the low roughness. Optimum hydrophobic (e.g. antigraffiti) properties of the SIL/PTFE system were obtained for the compositions of a regular spherical domain pattern at the surface with the minimum surface roughness. It occurred at about 20 - 45 wt. % of PTFE content in the system. It is suggested that the regular nanopattern of F atoms of PTFE and CH3 groups of crosslinked SIL component at the surface is immobilized by the semi-interpenetrating (semi-IPN) structures. The enrichment of the surface layers with immobilized F can be considered as a key factor for achieving excellent application results.